A Study on the Self-Sustaining Solar Module by Utilizing Solar Cell from Non-Degradable Waste - Farah Aina Mohd Jamal; Syarfa Najihah Raisin; Mus'ab Sahrim; Irneza Ismail; Sharma Rao Balakrishnan; Wan Zakiah Wan Ismail; Bushra Naeem; Abdullah Solihin Mohd Fauzi; Ahmad Syahmi Mohd Zain; Fatinah Mohd Rahalim; Nur Arina Hazwani Samsun ZainI; Juliza Jamaludin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Teknologi Nasional, 2024)
Non-Indexed Publication